2012
DOI: 10.3390/s121115036
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Structures and Properties of Organic Materials for Biosensors: An Overview

Abstract: The capabilities of biosensors for bio-environmental monitoring have profound influences on medical, pharmaceutical, and environmental applications. This paper provides an overview on the background and applications of the state-of-the-art biosensors. Different types of biosensors are summarized and sensing mechanisms are discussed. A review of organic materials used in biosensors is given. Specifically, this review focuses on self-assembled monolayers (SAM) due to their high sensitivity and high versatility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 132 publications
(118 reference statements)
0
30
0
1
Order By: Relevance
“…[73][74][75][76][77][78] Nanomaterials applied to electrochemical or optical immunoassays have been utilized in the detection of biomolecule activity. 8,9,79,80 Carbon nanomaterials, such as carbon-based nanotubes and nanofibers, have been amply discussed in the context of their aptness for the development of nanosensors. They all feature a number of characteristics, such as biocompatibility, chemical functionality and conductivity, which are suitable for the detection of biological interactions.…”
Section: Commonly Used Nanomaterialsmentioning
confidence: 99%
“…[73][74][75][76][77][78] Nanomaterials applied to electrochemical or optical immunoassays have been utilized in the detection of biomolecule activity. 8,9,79,80 Carbon nanomaterials, such as carbon-based nanotubes and nanofibers, have been amply discussed in the context of their aptness for the development of nanosensors. They all feature a number of characteristics, such as biocompatibility, chemical functionality and conductivity, which are suitable for the detection of biological interactions.…”
Section: Commonly Used Nanomaterialsmentioning
confidence: 99%
“…In another study, Tang et al demonstrated antigen-antibody interaction via GOD conjugated hollow gold-silver microspheres (AuAgHSs) further coupled using Prussian blue NPs (an artificial catalase), on a graphene-based immunosensor [117]. Pesticidal study [96] Hba1c biosensor Determining glycated hemoglobin [97] Piezoelectric biosensors Detecting carbamate and organophosphate [98] Uric acid biosensors Diagnosis of various clinical abnormalities or illness (e.g., diagnosis of cardiovascular disease) [99,100] Glucose oxidase electrode biosensors Measuring of glucose in biological sample of diabetic patient [101] Quartz-crystal biosensors Detection of proteins at ultrahigh-sensitive level in liquids [102] Optical Polyacrylamide based hydrogel biosensors Immobilization of biomolecules [30] Silicon biosensor For biosensing, bioimaging, and in cancer therapy [103,104] Microfabricated biosensor In novel drug delivery (e.g., in optical corrections) [105] Fluorescence tagged/Genetically encoded biosensor Investigation of various biological process and molecular systems in the cell [27,[106][107][108] Electrochemical or optical Nanomaterials biosensors For diagnosis and in drug delivery [32,93,[109][110][111][112][113][114] …”
Section: Glucose Monitoringmentioning
confidence: 99%
“…Searching for a functional nanostructure as the carrier for immobilization of the signal sources materials and antibody has always been the goal in fabricating ultrasensitive ECL immunoassay based on QDs [13]. The emergence of graphene nanosheets provides good opportunities for building highly-sensitive, highly-selective ECL immunosensors, because of its outstanding biocompatibility, good electron transfer, excellent adsorption capacity and large 2-D specific surface area [14,15]. Owing to these excellent properties, the graphene nanosheets is an ideal matrix to coimmobilize CdTe QDs and CA 19-9’s secondary antibody (CA 19-9 Ab2/CdTe-G), which can act as a signal tag to amplify the ECL signal.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of nanotechnology, various types of nanomaterials have been widely applied in the fabrication of immunosensor, such as metal nanoparticles [17], graphene (G) [15] and quantum dots (QDs) [14]. In recent years, nano ferromagnetic probes made of nano ferromagnetic oxide (such as Fe 3 O 4 ) material have been developed; they can controllably separate under an external magnetic field.…”
Section: Introductionmentioning
confidence: 99%